Towards a better understanding of people’s responses to renewable energy technologies: insights from Social Representations Theory - Batel, S.; Devine-Wright, P. (Public Understanding of Science, 2015)
In the past few years, social research has been examining what contributes to the attitude–behaviour gap in people’s responses to large-scale renewable energy technologies. The NIMBY explanation for the gap has long dominated that area of research, but has also been criticised. Alternative proposals to NIMBY were advanced, but it is still evident that some of those maintain presuppositions of NIMBY and that this area of research needs more integration, namely at a theoretical level. In this paper we argue that to overcome those aspects it is relevant, first, to situate the promotion of renewable energy production as a social change process in today’s societies, and, second, to therefore consider the socio-psychological aspects involved in people’s responses to social change. We discuss specifically how the Theory of Social Representations may help us with that and contribute to a better understanding of people’s responses to renewable energy technologies.